oil and the propensity to armed struggle in the niger delta region of nigeria - oyefusi aderoju (Policy research working paper ;, 2007)
The authors examine the influence of infrastructure, institutional quality, colonial and geographic context, and trade preferences on the pattern of bilateral trade. They are interested in threshold effects, and so emphasize those cases where bilateral country pairs do not actually trade. The authors depart from the institutions and infrastructure literature in this respect, using selection-based gravity modeling of trade flows. They also depart from this literature by mixing principal components (to condense the institutional and infrastructure measures) with a focus on deviations in the resulting indexes from expected values for given income cohorts to control for multicollinearity. The authors work with a panel of 284,049 bilateral trade flows from 1988 to 2002. Matching bilateral trade and tariff data and controlling for tariff preferences, level of development, and standard distance measures, they find that infrastructure and institutional quality are significant determinants not only of export levels, but also of the likelihood exports will take place at all. Their results support the notion that export performance, and the propensity to take part in the trading system at all, depends on institutional quality and access to well-developed transport and communications infrastructure. Indeed, this dependence is far more important, empirically, than variations in tariffs in explaining sample variations in North-South trade.